The Hydroalcoholic Extract Obtained from Mentha piperita L. Leaves Attenuates Oxidative Stress and Improves Survival in Lipopolysaccharide-Treated Macrophages - Mariana Oliveira Arruda; Saulo José Figueiredo Mendes; Simone Aparecida Teixeira; Ludmilla Santos Silva de Mesquita; Maria Nilce de Sousa Ribeiro; Stanley de Sousa Lima Galvão; Marcelo Nicolás Muscará; Elizabeth Soares Fernandes; Valério Monteiro-Neto (Journal of Immunology Research)
Mentha piperita L. (peppermint) possesses antimicrobial properties, but little is known of its ability to modulate macrophages. Macrophages are essential in bacterial infection control due to their antimicrobial functions and ability to link the innate and adaptive immune responses. We evaluated the effects of the peppermint leaf hydroalcoholic extract (LHAE) on cultured murine peritoneal macrophages stimulated or not with lipopolysaccharide (LPS) in vitro. Vehicle-treated cells were used as controls. The constituents of the extract were also identified. Epicatechin was the major compound detected in the LHAE. LPS-induced macrophage death was reversed by incubation with LHAE (1–30 μg/ml). Higher concentrations of the extract (≥100 μg/ml) decreased macrophage viability (49–57%) in the absence of LPS. LHAE (1–300 μg/ml) attenuated H2O2 (34.6–53.4%) but not nitric oxide production by these cells. At similar concentrations, the extract increased the activity of superoxide dismutase (15.3–63.5-fold) and glutathione peroxidase (34.4–73.6-fold) in LPS-treated macrophages. Only LPS-unstimulated macrophages presented enhanced phagocytosis (3.6–6.6-fold increase) when incubated with LHAE (3–30 μg/ml). Overall, the LHAE obtained from peppermint modulates macrophage-mediated inflammatory responses, by stimulating the antioxidant pathway in these cells. These effects may be beneficial when the excessive activation of macrophages contributes to tissue damage during infectious disease.